Early Emergency Medicine Milestone Assessment for Predicting First-Year Resident Performance - Rochelle L. Versalle; Brett R. Todd; Nai-Wei Chen; Danielle E. Turner-Lawrence (Association of American Medical Colleges, 2024)
Introduction The Accreditation Council for Graduate Medical Education (ACGME) requires emergency medicine (EM) residency training programs to monitor residents' progress using standardized milestones. The first assessment of PGY 1 resident milestones occurs midway through the first year and could miss initial deficiencies. Early assessment of PGY 1 EM resident milestones has potential to identify at-risk residents prior to standard midyear evaluations. We developed an orientation syllabus for PGY 1 residents followed by a milestone assessment. Assessment scores helped predict future milestone scores and American Board of Emergency Medicine (ABEM) In-Training Examination (ITE) scores for PGY 1 residents. Methods From 2013 to 2020, we developed and implemented Milestone Evaluation Day (MED), a simulation-based day and written exam assessing PGY 1 EM residents during their first month on the 23 ACGME 1.0 milestones. MED stations included a history and physical with verbal presentation, patient simulation, vascular access, wound management, and airway management. MED, Clinical Competency Committee-generated (CCC-generated) milestone, and ABEM ITE scores were averaged and compared utilizing Pearson's correlation coefficient. Results Of 112 PGY 1 EM residents, 110 (98%) were analyzed over an 8-year period. We observed a moderate positive correlation of MED and CCC-generated milestone scores (r = .34, p < .001). There was a nonstatistically significant weak positive correlation of MED and ABEM ITE scores (r = .13, p = .17). Discussion An early assessment of EM milestones in the PGY 1 year can assist in the prediction of CCC-generated milestone scores for PGY 1 residents.